2017
DOI: 10.1103/physrevlett.118.155101
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Kinetic Energy in the Energy Balance of a Solar Flare

Abstract: The energy released in solar flares derives from a reconfiguration of magnetic fields to a lower energy state, and is manifested in several forms, including bulk kinetic energy of the coronal mass ejection, acceleration of electrons and ions, and enhanced thermal energy that is ultimately radiated away across the electromagnetic spectrum from optical to x rays. Using an unprecedented set of coordinated observations, from a suite of instruments, we here report on a hitherto largely overlooked energy component-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 44 publications
(76 reference statements)
9
81
0
Order By: Relevance
“…Our results on the turbulent onset of fast magnetic reconnection support suggestions that turbulence might play a role in the energy transport and cascade in solar flares (Kontar et al 2017;Jeffrey et al 2018). While 2D MHD simulations show the dominance of tearing modes (Huang et al 2019), recent 3D MHD simulations show that in both externally driven (as in microflares discussed here in which the turbulence is externally driven by the interacting magnetic bipole) and internally developed cases, turbulence would suppress the formation of plasmoids, making turbulent reconnection the main reconnection process (Kowal et al 2009(Kowal et al , 2019.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Our results on the turbulent onset of fast magnetic reconnection support suggestions that turbulence might play a role in the energy transport and cascade in solar flares (Kontar et al 2017;Jeffrey et al 2018). While 2D MHD simulations show the dominance of tearing modes (Huang et al 2019), recent 3D MHD simulations show that in both externally driven (as in microflares discussed here in which the turbulence is externally driven by the interacting magnetic bipole) and internally developed cases, turbulence would suppress the formation of plasmoids, making turbulent reconnection the main reconnection process (Kowal et al 2009(Kowal et al , 2019.…”
Section: Resultssupporting
confidence: 84%
“…In addition, turbulence is proposed to be an energy transport process in solar flares (e.g. Kontar et al 2017;Jeffrey et al 2018). Its persistence and characteristics directly at the reconnection site, and its role in triggering fast reconnection, however, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…( 10 ) found that nonthermal broadening increased with temperature and height in the coronal loop top source. Another study showed that the nonthermal broadening of one line, formed at 16 MK in the corona, peaked before the acceleration of electrons in the “impulsive” phase of the flare ( 11 ). Further, the ratio of the turbulent kinetic energy to accelerated electron power gave a time scale for dissipating this turbulence of 1 to 10 s, similar to predictions of MHD models ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying driver for such particle acceleration events is generally understood to be the excess energy stored in stressed magnetic fields that is released via the process of magnetic reconnection. While this broad picture has been accepted for a while, it is only recently that observations have started to reveal some details (Kontar et al 2017) and simulations have started to establish the details of particle acceleration in reconnection regions (e.g., (Vlahos et al 2016;Arzner & Vlahos 2004;Dahlin et al 2015) and references therein). On the other hand, the possibility of small, ubiquitous reconnection events accelerating electrons and giving rise to the so-called nanoflares (Parker 1988) has gained considerable momentum as a candidate for coronal heating (e.g., (Klimchuk 2015;Barnes et al 2016) and references therein).Recent simulations have demonstrated the spontaneous development of current sheets with a high filling factor, even away from magnetic nulls ((Kumar et al 2015;Kumar & Bhattacharyya 2016)); these current sheets can serve as potential E-mail: tomin.james@students.iiserpune.ac.in sites for small electron acceleration events.…”
Section: Introductionmentioning
confidence: 99%